EFEKTIVITAS KEBIJAKAN PENGELOLAAN MANGROVE UNTUK MENDUKUNG MITIGASI PERUBAHAN IKLIM DI PROVINSI KALIMANTAN TIMUR - Mimi Salminah; Iis Alviya (Jurnal Analisis Kebijakan Kehutanan, 2019)
As a climate change mitigation action, East Kalimantan Province has targeted emission reduction from mangrove forest. Mangrove-related policies at national and local levels have been issued before and after the program execution. It is necessary to measure the effectiveness of the policies to identify potential challenges in its implementation, particularly from policy aspect. This analysis is required to support the Government in achieving the emission reduction target, so it would obtain payment compensation from World Bank by 2024. Effectiveness of the policies is analysed using Grindle Theory combined with climate change mitigation principles in mangrove management. The results show that there is still ineffective in implementing climate change mitigation on mangrove management including requirements for technical regulations determining the content of the issued policies, provision of one mangrove and land use data, and of green fish pond management options. Moreover, coordination among related sectors, raising awareness programs, and facilitation for local coastal community to apply sustainable mangrove management play significant role in the effectiveness of the implementation. In theory, the effectiveness of policy implementation is affected by clarity of policy content, both in conceptual and practical terms, through coordination and communication within related actors, both authorities and affected actors.